Evaluación global de la resistencia de los bananos al marchitamiento por Fusarium, enfermedades de las manchas foliares causadas por Mycosphaerella y nematodos: evaluación de comportamiento - Carlier, J.; Waele, D. de; Escalant, J-V.; Vézina, A.; Picq, C.; International Network for the Improvement of Banana and Plantain (2002)
This technical guidelines replace the technical guidelines 1 (Screening of Musa germplasm for resistance and tolerance to nematodes) and 3 (Evaluation of Musa germplasm for resistance to Sigatoka diseases and Fusarium wilt) as far as performance evaluations are concerned. Technical Guidelines for in-depth evaluations, which were also part of Technical Guidelines 3, are published separately. The Fusarium wilt and Mycosphaerella leaf spot sections have been updated following recommendations and comments made after analysing IMTP II results.